Edwards’ Natural Typology and the Problem of Subjectivity - Světlíková, Anna (Jonathan Edwards studies, 2013)
The article discusses Edwards’ theory of natural typology in his "Types" notebook with respect to the conception of the self that underlies the difficulty of Edwards’ argument. This is identified by Edwards himself and by modern critics as the problem of subjectivity, the difficulty of distinguishing between the believer’s subjective ideas and divinely warranted interpretations of the created world. In this perspective it can be argued…